(untitled) (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
This study analyses the Knowledge, Attitude, Practice (KAP) and Observation regarding hygiene, safety and handling of food and to assess the effect of nutrition education (with developed aids) on street beverage vendors (SBV, n =100). It was a randomized control trial in which street beverage vendors of Delhi, India was included. The SBV were divided into a control group (CG), n=50 (did not receive any nutrition education) and experimental group (EG), n=50. Nutrition education was given with the developed aids to the EG only. After one- month of intervention KAP was assessed again for both the groups. Results revealed Knowledge score was 10.90±3.85 (poor), Attitude score was - 6.44±5.65 (poor) Practice score was 8.47± 2.58 (poor) and observation score was 16.46± 4.74 (poor) of all SBV. At baseline both the groups (CG and EG) were comparable. Post nutrition education results showed an increase in the Knowledge of the EG (11.96 vs. 17.80, p=<0.01), the Attitude (-6.60 vs. 28.1±0.93, p=<0.01), Practice (9.22 vs. 18.62, p=<0.01) and observation (14.88 vs. 28.28, p=<0.01). The study concludes that KAPand Observation assessment scores were unsatisfactory, most of the vendors fell under the category of fair to poor scores. After the nutrition education program, the experimental group scored as compared to the control group.